2014
DOI: 10.1007/s10551-014-2313-6
|View full text |Cite
|
Sign up to set email alerts
|

MacIntyrean Virtue Ethics in Business: A Cross-Cultural Comparison

Abstract: This paper seeks to establish whether the categories of MacIntyrean virtue ethics as applied to business organizations are meaningful in a non-western business context. It does so by building on research reported in Moore (Organ Stud, 33(3): 363-387, 2012) in which the application of virtue ethics to business organizations was investigated empirically in the UK, based on a conceptual framework drawn from MacIntyre's work (After Virtue 2007). Comparing these results with an equivalent study in Sri Lanka, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 48 publications
(51 reference statements)
3
27
0
6
Order By: Relevance
“…While the mapping of corporate virtues identified above requires empirical verification, it does have several advantages over the alternative models that were reviewed above. As noted, its philosophical grounding, together with the empirical work already conducted on the basic mapping in Figure (see Moore ; Fernando & Moore ), gives it an initial credibility. In addition, it is in the nature of virtue ethics that it draws attention to character, character development, and by definition therefore has a narrative dimension.…”
Section: Discussionmentioning
confidence: 90%
“…While the mapping of corporate virtues identified above requires empirical verification, it does have several advantages over the alternative models that were reviewed above. As noted, its philosophical grounding, together with the empirical work already conducted on the basic mapping in Figure (see Moore ; Fernando & Moore ), gives it an initial credibility. In addition, it is in the nature of virtue ethics that it draws attention to character, character development, and by definition therefore has a narrative dimension.…”
Section: Discussionmentioning
confidence: 90%
“…So then, how are virtues developed? It is believed that through the deliberate and conscious attempt to live out the virtues, one achieves moral excellence (Arjoon, 2000;Fernando and Moore, 2015). Hence, virtue ethics theory believes that it is possible to learn, develop and acquire certain "proper" habits over time.…”
Section: Virtue Ethics Theorymentioning
confidence: 99%
“…Proponents have argued that the notion of virtue is not solely the property of Western philosophical thought, as the concept of doing the right thing or being virtuous is believed to span across cultures (Demuijnck, 2015;Koehn, 2013;Murphy, 1999). Motivated to explore the usefulness of MacIntyre's (2007) framework in another culture, Fernando and Moore (2015) found that the respondents interviewed in Sri Lanka demonstrated an understanding of the purpose of their organizations as cultivating internal goods, e.g., serving their internal and external stakeholders as well as being cognizant of the environment for the common good, and they believed that the pursuit of such internal goods first and foremost inevitably leads to external goods, such as financial performance and growth. While it is encouraging to see the potential cross-cultural applications of MacIntyrean virtue ethics, more research needs to be done in other cultural contexts.…”
Section: Virtue Ethics Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Not only has MacIntyre's conceptual framework been used as a basis for empirical studies in the West but also further afield in Sri Lanka (Fernando and Moore 2015), to see whether other polities may provide environments more "positively conducive to a practice-like mode of production" (Keat 2008, p. 83). This is clearly important for the general validity of MacIntyre's concepts since, as MacIntyre himself states, "the claims of such a theory must concern human rather than Chinese or Greek excellence" (MacIntyre 1991, p. 104).…”
Section: Introductionmentioning
confidence: 99%